Schistosomiasis Prevalence and Intensity of Infection in Latin America and the Caribbean Countries, 1942-2014: A Systematic Review in the Context of a Regional Elimination Goal. - Ana Clara Zoni; Laura Catalá; Steven K Ault (Public Library of Science (PLoS), 2016)
BACKGROUND:In 2012 the World Health Assembly adopted resolution WHA65.21 on elimination of schistosomiasis, calling for increased investment in schistosomiasis control and support for countries to initiate elimination programs. This study aims to analyze prevalence and intensity of Schistosoma mansoni infection in children in Latin America and the Caribbean countries and territories (LAC), at the second administrative level or lower. METHODOLOGY:A systematic review of schistosomiasis prevalence and intensity of infection was conducted by searching at PubMed, LILACS and EMBASE. Experts on the topic were informally consulted and institutional web pages were reviewed (PAHO/WHO, Ministries of Health). Only SCH infection among children was registered because it can be a 'proxi-indicator' of recent transmission by the time the study is conducted. PRINCIPAL FINDINGS:One hundred thirty two full-text articles met the inclusion criteria and provided 1,242 prevalence and 199 intensity of infection data points. Most of them were from Brazil (69.7%). Only Brazil published studies after 2001, showing several 'hot spots' with high prevalence. Brazil, Venezuela, Suriname and Saint Lucia need to update the epidemiological status of schistosomiasis to re-design their national programs and target the elimination of Schistosoma mansoni transmission by 2020. In Antigua and Barbuda, Dominican Republic, Guadeloupe, Martinique, Montserrat and Puerto Rico schistosomiasis transmission may be interrupted. However the compilation of an elimination dossier and follow-up surveys, per WHO recommendations, are needed to verify that status. Hence, the burden of subtle SCH chronic infection may be still present and even high in countries that may have eliminated transmission. Heterogeneity in the methodologies used for monitoring and evaluating the progress of the schistosomiasis programs was found, making cross-national and chronological comparisons difficult. CONCLUSIONS:There is a need for updating the schistosomiasis status in the historically endemic countries and territories in LAC to address the required public health interventions for control and elimination programs or to verify the elimination of transmission of Schistosoma mansoni. Improved reporting and standardization of the monitoring and evaluation methodologies used are recommended, while using available WHO guidelines. Meeting a regional elimination goal will require additional and improved epidemiological data by age group and sex.